2015
DOI: 10.1515/helmin-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

The helminth fauna of Apathya cappadocica (Werner, 1902) (Anatolian Lizard) (Squamata: Lacertidae) from Turkey

Abstract: SummaryA total of thirty-one Anatolian Lizard, Apathya cappacocica, samples from several provinces of Eastern and South-Eastern Turkey were examined for helminths. Two species of Nematoda, including Spauligodon atlanticus, Skrjabinodon medinae; two species of Cestoda, including Mesocestoides sp. tetrahydia and Oochoristica tuberculata and one species of Acanthocephala, Centrorhynchus sp. were found. This is the fi rst helminth record of A. cappodocica from Turkey. A. cappadocica represents a new host record fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…aegyptiacus from Chalcides ocellatus (Incedogan et al, 2014). This species was reported from Apathya cappadocica (Birlik et al, 2015). This is the third report for Sk.…”
Section: Oxyurida: Pharyngodonidae Skrjabinodon (Inglis 1968) Skrjabmentioning
confidence: 73%
See 3 more Smart Citations
“…aegyptiacus from Chalcides ocellatus (Incedogan et al, 2014). This species was reported from Apathya cappadocica (Birlik et al, 2015). This is the third report for Sk.…”
Section: Oxyurida: Pharyngodonidae Skrjabinodon (Inglis 1968) Skrjabmentioning
confidence: 73%
“…Cestoidea Cyclophyllidea: Anoplocephalidae Oochoristica tuberculata (Rudolphi, 1819) Lühe, 1898 In our study, this species was observed in only two hosts (6%). This species was reported from Paralaudakia caucasia (Yıldırım-han et al, 2006), Lacerta trilineata (Yıldırımhan et al, 2011), Chalcides ocellatus (Incedogan et al, 2014) and Apathya cappadocica (Birlik et al, 2015) from several localities in Turkey. This report is the fi fth for O. tuberculata from reptiles in Turkey.…”
Section: Prosthodendrium Chilostomum (Mehlis 1831)mentioning
confidence: 92%
See 2 more Smart Citations
“…The species which have been studied for their helminth fauna are: Lacerta viridis (Schad et al, 1960), Podarcis tauricus (Schad et al, 1960), Parvilacerta parva (Saygı & Olgun, 1993), Anatololacerta danfordi (Gürelli et al, 2007), Lacerta trilineata (Yıldırımhan et al, 2011), Eremias pleskei, E. strauchi , E. suphani (Düsen et al . 2013), Apathya cappadocica (Birlik et al, 2015), Darevskia rudis (Roca et al, 2015a), Darevskia uzzelli , D . bendimahiensis and D .…”
Section: Introductionmentioning
confidence: 99%